Effect of tillage methods and nitrogen management practices on soil mineral nitrogen and grain protein, and yield of wheat (Triticum aestivum)in rice (Oryza sativa)-wheat system - S, SUDARSHAN; SHEKHAWAT, KAPILA; RATHORE, S S; M P, NIVEDITHA; SUPRIYA (The Indian Journal of Agricultural Sciences, 2024)
The field experiment was carried out during winter (rabi) season of 2020–21 at ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of tillage methods and nitrogen management practices on soil mineral nitrogen and grain protein and yield of wheat in rice- wheat system. The experiment was laid out in a split plot design (SPD), where the main plots included 4 different crop establishment methods, and the sub-plots tested 4 nitrogen management strategies that were replicated thrice. The results showed that, residue retention in zero tillage recorded significantly (P<0.05) higher soil mineral nitrogen, protein content in grain (12.6%) and grain yield (4.99 t/ha) over other treatments. Similar results also recorded under different nitrogen management practices, where leaf colour chart (LCC)-guided N application has significantly (P<0.05) higher soil mineral nitrogen, grain protein content (12.9%) and grain yield (5.39 t/ha) over remaining treatments. The LCC-guided N application in residue retained (3 t/ha) ZT practices can be recommended in wheat under rice- wheat system for higher soil mineral nitrogen availability, improving grain protein content and productivity.